Mad or bad? : a critical approach to counselling and forensic psychology - Vossler, Andreas; Havard, Catriona; Pike, Graham, (Professor of forensic cognition); Barker, Meg-John, 1974-; Raabe, Bianca (Los Angeles : SAGE, 2017)
Is an offender with mental health problems fully responsible for their offences? Should certain criminal behaviours be treated with incarceration and rehabilitation - or counselling and psychotherapy? This book asks these questions, and more. It is a cutting-edge text that provides a comprehensive introduction to mental health problems and criminal behaviour, and considers the most common and effective therapeutic approaches for working with offenders and victims of crime.
Includes bibliographical references and index.
Keywords: Forensic psychology; Counseling